Advancements in the characterisation of oligonucleotides by high performance liquid chromatography‐mass spectrometry in 2021: A short review. Issue 3 (10th April 2022) - Hannauer, Fabien; Black, Rachelle; Ray, Andrew D.; Stulz, Eugen; Langley, G. John; Holman, Stephen W.
Abstract: The first oligonucleotide therapeutic was approved by the Food and Drug Administration in 1998, and since then, 12 nucleic acids have been commercialised as medicines. To be approved, the oligonucleotides need to be identified and characterised as well as its related impurities. Different methods exist, but the most commonly used is ion‐pairing reversed‐phase liquid chromatography with tandem mass spectrometry. The separation obtained depends on the mobile phase and column used. Other methods have been developed, notably by using hydrophilic interaction chromatography and two‐dimensional high performance liquid chromatography. Furthermore, ion‐pairing reversed‐phase high performance liquid chromatography ultra‐violet spectroscopy detection and mass spectrometry has been optimised for the analysis of methylated nucleobases due to the utilisation of this modification in the drugs. This review covers the recent advancements in the analysis and characterisation of oligonucleotides in 2021 by high performance liquid chromatography mass spectrometry, notably by hydrophilic interaction chromatography and two‐dimensional liquid chromatography but also the different parameters that influence the analysis by ion‐pairing reversed‐phase high performance liquid chromatography, the characterisation of methylated nucleobases, and the recent software developed for oligonucleotides.